The art of mixing a visual guide to recording, engineering, and production - Gibson, David 1957- (Mix pro audio series, 2005)
A revised full-color edition with even more examples of musical styles visually illustrated to reveal how sound "looks" in a professionally mixed song. This volume provides insight into how sound works in a three-dimensional field, helping the reader understand how to apply mixing techniques to their own recordings.